Gross National Happiness sebagai Indikator Kesejahteraan Indonesia - Silverius Yoseph Soeharso; Yusuf Hadi Yudha; Evanytha (Fakultas Psikologi Universitas Pancasila, 2011)
Basically, development is not only about material aspect, but also human aspect. It needs other indicators to achieve welfare. Happiness can be used as a tool to achieve welfare. The rise in Gross Domestic Product (GDP) must be balanced by the increase of Gross National Happiness (GNH). The indicators of GNH are: (1) Life security such as sufficient piece of land, permanent house, and enough food; (2) Physical and mental health; (3) Supportive family where a person lives with all family member, has a job, and there is compassion and understanding; (4) Strong community, (5) Good environment including prosperous land, enough water, animals, free poison area, street, drinking water, electricity; (6) Freedom including ability to do something without harm others, free from debt; (7) Self-pride including including succeed family, successful career; (8) Access to dharma; comprise of peaceful life, self-content, and help others. From the result of GNH scale testing, the coefficient alpha was obtained at 0.791. From testing 47 items, there were 31 valid items. These items were developed from GNH indicators. These indicators actually had been discussed in seminar on GNH at the Asian Institute of Technology. Overall these items are able to be implemented in Indonesia.